2018
DOI: 10.1111/bjhp.12310
|View full text |Cite
|
Sign up to set email alerts
|

Using efficacy cues in persuasive health communication is more effective than employing threats – An experimental study of a vaccination intervention against Ebola

Abstract: The data support the assumption that there is an important association between threat and coping appraisals facilitating behaviour change. Moreover, the widely held notion that people have to be scared or threatened to encourage attitude and behaviour changes should be treated with caution. Communication should instead focus on efficacy to foster adaptive responses. Statement of contribution What is already known on this subject? There is mixed support for the effectiveness of fear appeals in persuasive health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 52 publications
5
51
0
Order By: Relevance
“…In summary, a fear-arousing frame involves the danger of producing unwanted fear-control responses that can lead to subsequent maladaptive behavior. These findings are consistent with previous research (Ort & Fahr, 2018;Ruiter et al, 2014;Tannenbaum et al, 2015;Witte & Allen, 2000) and speak against the imprudent use of such appeals. In contrast, a positive emotional frame (e.g., via humor) induced joy, which had beneficial effects.…”
Section: Full Papersupporting
confidence: 92%
See 1 more Smart Citation
“…In summary, a fear-arousing frame involves the danger of producing unwanted fear-control responses that can lead to subsequent maladaptive behavior. These findings are consistent with previous research (Ort & Fahr, 2018;Ruiter et al, 2014;Tannenbaum et al, 2015;Witte & Allen, 2000) and speak against the imprudent use of such appeals. In contrast, a positive emotional frame (e.g., via humor) induced joy, which had beneficial effects.…”
Section: Full Papersupporting
confidence: 92%
“…It is expected that this emotional wrapping of health risks affects the primal fear response and influences further information processing and decision making. The beneficial effects of this emotional framing can be manifold: it can, e.g., reduce reactance or improve message judgment (Forgas, 1995;Forgas & Koch, 2013;Ort & Fahr, 2018). Nabi (2016) also stresses that positive messages can increase individuals' motivation to change their behavior to overcome threat perceptions.…”
Section: Full Papermentioning
confidence: 99%
“…Achar et al 44 reported that the purpose of a fear appeal during a disease outbreak is to encourage the practice of disease prevention behavior by individuals. Moreover, Smith et al 45 126 the use of hearing protection, eg, hearing protection in construction workers. They found that, when a fear appeal was used to encourage the use of hearing protection, use of hearing protection was more likely in individuals who perceived that the threat of noise-induced hearing loss was high and had high self-efficacy compared to those who perceived that the threat was low and had low selfefficacy.…”
Section: Fear Arousal and Prevention Behaviormentioning
confidence: 99%
“…The behavior intention of participants in the danger control group was significantly higher than that in the fear control group (t(150) = 3.65, p < .001), which was theoretically consistent with the basic frame of the EPPM. Given that these analyses were not registered beforehand, and that the discriminating value approach has been criticized for its flawed conceptual logic (Ort & Fahr, 2018), we do not consider it appropriate to make a conclusion on the EPPM's validity in the present study. Instead, we suggest treating the result's limited implication as a mere reference or a hint when discussing the relation between perceived threat and behavior intention.…”
Section: Discussionmentioning
confidence: 97%
“…According to the EPPM's interpretation, high threat and low efficacy would lead to fear control process where people try to control their fear instead of taking efficient actions, while high threat and high efficacy would result in danger control process where people take efficient actions to avert threat. To the best of our knowledge, there is limited research using SEM to test the EPPM, except for a study conducted by Ort and Fahr's (2018). Considering that the differences in analysis strategies may bring us new insights into the result of the nonsignificant path from perceived threat to behavior intention, we would discuss the results compared with other analysis strategies mentioned in previous research.…”
Section: Discussionmentioning
confidence: 99%